2015
DOI: 10.1097/meg.0000000000000351
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of anticoagulation therapy with different doses of enoxaparin for portal vein thrombosis in cirrhotic patients with hepatitis B

Abstract: Anticoagulation therapy with different doses of enoxaparin for PVT in hepatitis B patients with cirrhosis is efficient and safe, and 1 mg/kg enoxaparin subcutaneously every 12 h is a better anticoagulation regimen in the treatment of PVT in cirrhotic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 28 publications
7
73
0
3
Order By: Relevance
“…These responders had regression of their liver disease when compared directly to the 14 non-responders. Similar to Villa et al [21] , Cui et al [22] found no episodes of variceal hemorrhage, however, they did find much higher rates of non-variceal bleeding (6.4%-23.5%). While this study has several limitations including its generalizability as it only enrolled hepatitis B patients in China, it is nonetheless promising.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…These responders had regression of their liver disease when compared directly to the 14 non-responders. Similar to Villa et al [21] , Cui et al [22] found no episodes of variceal hemorrhage, however, they did find much higher rates of non-variceal bleeding (6.4%-23.5%). While this study has several limitations including its generalizability as it only enrolled hepatitis B patients in China, it is nonetheless promising.…”
Section: Discussionsupporting
confidence: 49%
“…Additionally, the authors demonstrated less hepatic decompensation in the low molecular weight heparin arm (P < 0.0001) and a more importantly, a significant survival benefit [21] . Building on this work, Cui et al [22] published their single center randomized trial of 65 patients investigating therapeutic doses of low-molecular weight heparin (1 mg/kg every twelve hours or 1.5 mg/kg daily), where 78.5% (n = 51) responded to treatment with either complete or partial recanalization at 6 mo after starting therapy. These responders had regression of their liver disease when compared directly to the 14 non-responders.…”
Section: Discussionmentioning
confidence: 99%
“…56,57 Enoxaparin can be used at either doses of 1 mg/kg subcutaneously every 12 hours or 1.5 mg/kg daily. 58 …”
Section: Thrombosismentioning
confidence: 97%
“…An antithrombotic therapy consistent with general principles is of crucial significance for treatment of visceral vein thrombosis [4,5]. Surgical treatment is justified in case of presence of peritoneal signs, or in case of suspected bowel wall necrosis, before signs of peritoneal irritation develop.…”
Section: The Following Are Mentioned As Aetiology Factors Of Visceralmentioning
confidence: 99%